De la furia como lugar epistémico: la filosofía y el arte de vanguardia como formas de crítica a la vida cotidiana. - Retana, Camilo (2012)
In this article I intend to problematize the role –overdimensioned– that has been assigned in the classic theory to the rationality. For this I struggle with the common argument according to which the senses trouble the cognitive processes. In my alternative proposal to that epistemology I present the fury as main category. In the text I debate that such ethical-epistemic tool, which precedence is imminently emotional, would not only trouble the cognitive procedures but on the opposite would overpower them (particularly those related to the criticism of the hegemonic moral systems). As examples of this critic to the rationality and of this defense to the fury I present some manifestations of vanguards art and some philosophical ideas of non –rationalist philosophers.